NETWORK ORGANIZATION OF SOCIETY IN THE CONTEXT OF THE MODERN CRITICAL THEORY - Овчелупова, О. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The problem of network organization society in the context of modern critical theory is examined in the article.